2013
DOI: 10.1002/etep.1736
|View full text |Cite
|
Sign up to set email alerts
|

Simplified parameter-less fault locator using double-end synchronized data for overhead transmission lines

Abstract: SUMMARYIn this paper, a new double‐end fault locator is presented for transmission lines. The fault location is achieved using synchronized measurement data and applying the least error squares (LSQ) principles disregarding the line parameters. The LSQ is applied on the positive sequence equivalent circuit to locate the fault distance. The proposed algorithm is non‐iterative and simple as it is derived from the lumped parameter fault locator model. Due to using double‐end data, the algorithm provides promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…On the other hand, fault location determination methods used for transmission lines may not be easily applicable in distribution systems because of the taps, distributed loads, and fault impedances. 3,4 Several methods were proposed in the literature to estimate the fault distance in distribution systems with either primitive or measurement-based methods. Primitive fault location methods identify the faulted section via either customer calls or clarifying switching status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, fault location determination methods used for transmission lines may not be easily applicable in distribution systems because of the taps, distributed loads, and fault impedances. 3,4 Several methods were proposed in the literature to estimate the fault distance in distribution systems with either primitive or measurement-based methods. Primitive fault location methods identify the faulted section via either customer calls or clarifying switching status.…”
Section: Discussionmentioning
confidence: 99%
“…They include shortening maintenance time, resulting in quick service restoration. On the other hand, fault location determination methods used for transmission lines may not be easily applicable in distribution systems because of the taps, distributed loads, and fault impedances . Several methods were proposed in the literature to estimate the fault distance in distribution systems with either primitive or measurement‐based methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, these parameters may not be known precisely and they can change with different line loading and weather conditions, which may adversely impact the accuracy of the fault location calculations. In recent years, several papers have been published in which methods of eliminating the negative impact of the line parameters on fault location calculations have been investigated [14], [15], [16], [17], [18], [19]. In each of these cases, the authors developed parameter-free fault location algorithms that were found to deliver accurate calculations of the fault distance when tested with computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that grid faults (symmetrical and asymmetrical) are generated by abnormal grid conditions such as phase‐to‐phase or phase‐to‐ground short circuits. The manifestation of these faults at the point of common coupling (PCC) of the REGS depends on the characteristics of the line and the transformers between the fault location and the PCC .…”
Section: Introductionmentioning
confidence: 99%